An Evaluation of Interindividual Responses to the Orally Administered Neurotransmitter β-Alanine. (23rd June 2013) - MacPhee, Sarah; Weaver, Ian N.; Weaver, Donald F.
Abstract : Previously, we have identified β -alanine as a potential endogenous anticonvulsant molecule. β -Alanine occurs within the human central nervous system and has been identified as both an inhibitory neuromodulator and neurotransmitter that is bioavailable to brain after oral administration. During preliminary compounding trials to ascertain dosing strategies for β -alanine, we noted pronounced differences in the side effect profile experienced by individuals of Asian and Caucasian descent. To investigate whether ethnicity affects β -alanine-induced side effects, we administered 3 g of β -alanine in 200 mL of fruit drink to ten people of each ethnic background and observed them for 30 minutes. Data collected included basic physical statistics (height, age, and weight) and descriptions of all side effects, as reported by participants. We found that participants of Asian descent experienced paraesthesia, but significantly different in time of onset, intensity, and anatomical localization, as compared to the effects experienced by Caucasian participants. Since β -alanine is an endogenous neurotransmitter substance within human brain, these side effect differences were unexpected.